Sea surface temperature variation linked to elemental mercury concentrations measured on Mauna Loa. Issue 14 (30th July 2016) - Carbone, F.; Landis, M. S.; Gencarelli, C. N.; Naccarato, A.; Sprovieri, F.; De Simone, F.; Hedgecock, I. M.; Pirrone, N.
Abstract: The Hg 0 time series recorded at the Mauna Loa Observatory (MLO) in Hawaii between 2002 and 2009 has been analyzed using Empirical Mode Decomposition. This technique has been used in numerous contexts in order to identify periodical variations in time series data. The periodicities observed in the tropical Pacific sea surface temperature (SST), through the data collected from five buoys, are also observed in Hg 0 concentrations and the relative humidity measured at the MLO. The lag times in the observed periodicities are related to the position of the buoys with respect to the measurement site. This demonstrates a direct link between climatological phenomena, in this case SST, and measured Hg 0 and reflects the influence of ocean SST on Hg 0 evasion. This is the first long‐term experimental evidence of such a direct effect on Hg 0 evasion from the oceanic surface driven by temperature. Key Points: Long‐term periodicity is seen in the atmospheric Hg time series measured on Mauna Loa, correlated with RH, anticorrelated with O3 The periodicity seen in the Hg time series is also correlated with the SST data from buoys along the equator and nearby Hawaii Physical variables related to large‐scale teleconnection phenomena should be taken into account when interpreting (Hg) time series